1985
DOI: 10.1063/1.865085
|View full text |Cite
|
Sign up to set email alerts
|

Fueling and heating of tandem mirror end cells using rf at the ion-cyclotron frequency

Abstract: Fueling and heating of tandem mirror end cells by rf at the ion-cyclotron frequency have been studied experimentally in the Phaedrus Tandem Mirror. The end cell density is found to increase linerly with rf voltage. The total plasma energy is observed to increase with rf power with no evidence of saturation at high power. The plasma axial length decreases with increasing rf power down to a length of approximately the distance between the two resonance locations in the end cell. The highest density and average i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…The basic idea of transverse heating of charged particles through cyclotron resonance is well known and has been studied extensively in labora tory plasmas (Hooke and Rothman, 1964; Eldridge, 1972;Golovato et al, 1985; and references therein). However, in most laboratory applications, the charged particles are generally heated by a narrow band of cyclotron waves at specific locations within a confinement device.…”
Section: Broad Band Electromagnetic Ion Cyclotron (Emic) Resonance Hementioning
confidence: 99%
“…The basic idea of transverse heating of charged particles through cyclotron resonance is well known and has been studied extensively in labora tory plasmas (Hooke and Rothman, 1964; Eldridge, 1972;Golovato et al, 1985; and references therein). However, in most laboratory applications, the charged particles are generally heated by a narrow band of cyclotron waves at specific locations within a confinement device.…”
Section: Broad Band Electromagnetic Ion Cyclotron (Emic) Resonance Hementioning
confidence: 99%
“…These energetic particle fluxes are coincident with intense, low-frequency auroral-zone turbulence, 7 and it has been suggested 8 that wave-particle interaction with this turbulence is responsible for the transverse acceleration of the ions to form the observed conies. Based on the laboratory study of transverse heating of ions through cyclotron resonance, 9 Chang et a/. 8 found that if the turbulence contained a modest fraction of lefthand-polarized waves, then its observed amplitude could easily account for the energies of the measured conies, making this even an ideal one for our detailed scrutiny.…”
mentioning
confidence: 98%
“…Ion cyclotron resonance heating, ICRH, has been used on many magnetic confinement experiments 27 ' 28 -29 ' 30 ' 3132 ' 33 ' 34,35 , with varied results. This technique is used to add energy to the ions by creating a electric field rotating at a frequency near the cyclotron frequency in the plasma.…”
Section: Description Of Icrh Systemmentioning
confidence: 99%